The queen conch mitogenome: intra- and interspecific mitogenomic variability in Strombidae and phylogenetic considerations within the Hypsogastropoda - Salima Machkour-M’Rabet (Nature Portfolio, 2021)
Abstract Aliger gigas is an economically important and vulnerable marine species. We present a new mitogenome of A. gigas from the Mexican Caribbean and use the eight publicly available Strombidae mitogenomes to analyze intra- and interspecific variation. We present the most complete phylogenomic understanding of Hypsogastropoda to date (17 superfamilies, 39 families, 85 genera, 109 species) to revisit the phylogenetic position of the Stromboidea and evaluate divergence times throughout the phylogeny. The A. gigas mitogenome comprises 15,460 bp including 13 PCGs, 22 tRNAs, and two rRNAs. Nucleotide diversity suggested divergence between the Mexican and Colombian lineages of A. gigas. Interspecific divergence showed high differentiation among Strombidae species and demonstrated a close relationship between A. gigas and Strombus pugilis, between Lambis lambis and Harpago chiragra, and among Tridentarius dentatus/Laevistrombus canarium/Ministrombus variabilis. At the intraspecific level, the gene showing the highest differentiation is ATP8 and the lowest is NAD4L, whereas at the interspecific level the NAD genes show the highest variation and the COX genes the lowest. Phylogenomic analyses confirm that Stromboidea belongs in the non-Latrogastropoda clade and includes Xenophoridea. The phylogenomic position of other superfamilies, including those of previously uncertain affiliation, is also discussed. Finally, our data indicated that Stromboidea diverged into two principal clades in the early Cretaceous while Strombidae diversified in the Paleocene, and lineage diversification within A. gigas took place in the Pleistocene.